Perlindungan Hukum bagi Konsumen dalam Transaksi E-Commerce Jual Beli Burung Kicauan di Surakarta - Wahyusaputri, Vanessa Maharani; Nugroho, Asianto; Hermawan, Sapto (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The online buying and selling of songbirds in Surakarta has grown significantly with the rise of e-commerce, offering convenience, efficiency, and broader market access. Consumers can easily browse and purchase birds through various online platforms without geographical limitations. However, this type of transaction also presents several risks, including fraud, uncertainty about the bird’s quality, and potential issues during shipping, such as injury or death. Legal protection for consumers engaging in online transactions is regulated under Law No. 8 of 1999 on Consumer Protection (UUPK) and Law No. 11 of 2008, amended by Law No. 19 of 2016, on Electronic Information and Transactions (UU ITE). These regulations outline the rights and obligations of both business actors and consumers to ensure fair and secure transactions. Despite the benefits of online transactions, challenges such as lack of transparency, unreliable sellers, and logistical issues remain prevalent. Consumers are advised to conduct transactions with reputable sellers, such as members of bird enthusiasts’ communities, to reduce the risk of fraud. Additionally, in cases of consumer losses, dispute resolution mechanisms are available through e-commerce complaint services or institutions such as the Consumer Dispute Settlement Agency (BPSK), Consumer Protection Organizations (LPKSM), and the Indonesian Consumers Foundation (YLKI). As online commerce continues to evolve, strengthening consumer protection mechanisms is essential to creating a more secure and reliable marketplace for songbird enthusiasts.